Influence of infrared final cooking on color, texture and cooking characteristics of ohmically pre-cooked meatball. (April 2016) - Yildiz Turp, Gulen; Icier, Filiz; Kor, Gamze
Abstract: The objective of the current study was to improve the quality characteristics of ohmically pre-cooked beef meatballs via infrared cooking as a final stage. Samples were pre-cooked in a specially designed-continuous type ohmic cooker at a voltage gradient of 15.26 V/cm for 92 s. Infrared cooking was then applied to the pre-cooked samples at different combinations of heat fluxes (3.706, 5.678, and 8.475 kW/m 2 ), application distances (10.5, 13.5, and 16.5 cm) and application durations (4, 8, and 12 min). Effects of these parameters on color, texture and cooking characteristics of ohmically pre-cooked beef meatballs were investigated. The appearance of ohmically pre-cooked meatball samples was improved via infrared heating. A dark brown layer desired in cooked meatballs formed on the surface of the meatballs with lowest application distance (10.5 cm) and longest application duration (12 min). The texture of the samples was also improved with these parameters. However the cooking yield of the samples decreased at the longest application duration of infrared heating. Highlights: Ohmic-Infrared combination system was developed to cook meatball. Infrared cooking improved the appearance of ohmically pre-cooked meatball. Application of lowest distance and longest duration of infrared improved color.